Why rearrange into a limited company? - Ahlbin, Elena (2016)
The most common legal business form among farmers is the sole proprietorship. However, during the last decades the number of farms managed as limited companies has increased in Sweden whilst the total number of farms has decreased. The differences between owning a limited company and having a sole proprietorship are substantial. The requirements of formality are more extensive, there is differences tax wise and in how business ownership and private equity can be structured and organized, as well as the personal liability for payments and financial risk.